Pigmented villonodular synovitis. Issue 12 (December 1991) - Givon, U; Ganel, A; Heim, M
Abstract : Pigmented villonodular synovitis (PVS) is an uncommon, usually monoarticular disorder encountered mainly in adults. A boy and a girl, both 7 years old, were referred because of recurrent knee effusions. Both were medically treated for other rheumatic disorders for five years. PVS was diagnosed by arthroscopy and synovectomy was curative in both cases.